Settlement of Child Criminal Cases of Terrorism Criminals through Restorative Justice (Al-Isti'adah) in Islamic Criminal Law - Muhammad Firman Akhsani; Mhd Yadi Harahap (ISNU Sumatera Utara, 2024)
The case of a child perpetrator of a terrorism crime raises complex problems related to law enforcement and child protection. The social, psychological, and moral impact of acts of terrorism on victims and societies requires an approach that is not only repressive, but also educational and restorative. Islamic criminal law offers the principles of justice and rehabilitation through the concept of al-isti'adah, which emphasizes the restoration of wrongs, moral construction, and the restoration of social harmony. This study aims to analyze the settlement of child cases of terrorism perpetrators through al-isti'adah-based restorative justice in Islamic criminal law. The research also assesses the relevance of Islamic legal principles with national laws and regulations related to child protection and the eradication of terrorism crimes. The research method used is normative, with a literature study and document analysis approach. Data sources include the Quran, Hadith, Indonesian laws and regulations, ulema fatwas, legal literature, and relevant previous research. The analysis was carried out qualitatively using content analysis techniques, mapping norms, restorative justice principles, and the application of al-isti'adah in the context of children of perpetrators of terrorism crimes. The results of the study show that the al-isti'adah-based restorative justice approach allows the restoration of relationships between perpetrators, victims, and society, as well as providing moral and spiritual education for children. The involvement of families, communities, and law enforcement is a key factor in the success of rehabilitation. The integration of Islamic legal principles with the Child Protection Law and the Terrorism Eradication Law has resulted in a humane, proportionate, and effective law enforcement mechanism in preventing recidivism. In conclusion, the al-isti'adah-based restorative justice model provides comprehensive solutions for the resolution of child cases of terrorism perpetrators, prioritizing social recovery, moral education, and the reintegration of children into society.